Computational pulsatile flow and efficiency analysis of biocompatible microfluidic artificial lungs for different fiber configurations - Asiltürk, Ahmet Yusuf. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
Average-sized microfluidic artificial lungs consisting of rows and columns of fiber bundles with the different column to row aspect ratios (AR) are numerically analyzed for flow characteristics, maximum gas transfer performance, minimum pressure drop, and proper wall shear stress (WSS) values in terms of biocompatibility. The flow is fully laminar and assumed to be incompressible. The problem is solved with both Newtonian and Non-Newtonian Carreau models. The transport analysis is performed using a combined convection-diffusion model, and the numerical simulations are carried out with the finite element method. The inlet volumetric flow is modeled as a sinusoidal wave function to simulate the cardiac cycle and its effect on the device performance. The model is first validated with experimental studies in steady-state condition and compared with existing correlations for transient conditions. Then, the validated model is used for a parametric study in both steady and pulsatile flow conditions. The results show that increasing the aspect ratio in fiber configuration leads to converging gas transfer rate, higher pressure drop, and higher WSS. While determining the optimum configuration, the acceptable shear stress levels play a decisive role to ensure biocompatibility. Also, it is observed that the steady analysis underestimates the gas transfer for higher aspect ratios. The Newtonian model finds the pressure drop and shear stress values less than the Carreau model. In contrast, the oxygen transfer performance observed in the Newtonian model is overestimated approximately by 5% compared to the Carreau model predictions.
Keywords: Fiber optics.; Microfluidic devices.